2016
DOI: 10.1038/ncomms12865
|View full text |Cite
|
Sign up to set email alerts
|

Lateral opening in the intact β-barrel assembly machinery captured by cryo-EM

Abstract: The β-barrel assembly machinery (BAM) is a ∼203 kDa complex of five proteins (BamA–E), which is essential for viability in E. coli. BAM promotes the folding and insertion of β-barrel proteins into the outer membrane via a poorly understood mechanism. Several current models suggest that BAM functions through a ‘lateral gating' motion of the β-barrel of BamA. Here we present a cryo-EM structure of the BamABCDE complex, at 4.9 Å resolution. The structure is in a laterally open conformation showing that gating is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

23
309
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(333 citation statements)
references
References 64 publications
(152 reference statements)
23
309
1
Order By: Relevance
“…Consistent with this model, engineered disulfide bonds that prevent the opening of the putative lateral gate are lethal in E. coli (17). Disulfide locking of the BamA b-barrel, however, does not effectively block OMP assembly in vitro (16,18,19). Molecular dynamics simulations (20, 21) and other studies (22) that suggest that the BamA β-barrel causes thinning of the adjacent membrane have led to an alternative model in which the Bam complex catalyzes OMP assembly by creating a local deformation of the lipid bilayer.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Consistent with this model, engineered disulfide bonds that prevent the opening of the putative lateral gate are lethal in E. coli (17). Disulfide locking of the BamA b-barrel, however, does not effectively block OMP assembly in vitro (16,18,19). Molecular dynamics simulations (20, 21) and other studies (22) that suggest that the BamA β-barrel causes thinning of the adjacent membrane have led to an alternative model in which the Bam complex catalyzes OMP assembly by creating a local deformation of the lipid bilayer.…”
mentioning
confidence: 56%
“…The complex has the shape of a top hat in which the BamA bbarrel forms the crown and the POTRA domains together with the lipoproteins form a brim (14,15). Based on the structure, it has been proposed that the rotation of the ring-like structure formed by the periplasmic elements of the Bam complex leads to the opening of an unstable junction between the first and last β-strands of the BamA b-barrel ("lateral gate") and thereby promotes the insertion of OMPs into the lipid bilayer in a stepwise fashion (14)(15)(16). The lipoprotein ring would create a protective environment that shields OMPs from repulsive interactions with periplasmic lipid head groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall structure was found in a bent L-shaped conformation, closely resembling that of POTRA3-5 of E. coli BamA (26,39,40). All three POTRA domains contained the conserved βααββ fold observed in other POTRA domains with relatively good structural alignment (23,47,48). Interestingly, the previously observed ∼40-residue insertion within Toc75 POTRA2 (17) overlaps with an extended α-helix encompassing residues 275-296, which we refer to as the P2-helix.…”
Section: Discussionmentioning
confidence: 82%
“…Recent X-ray crystallography and cryo-EM studies reported the structures of several Omp85 family members, including FhaC, TamA, and BamA (28,(36)(37)(38)(43)(44)(45)(46)(47). Given the conservation of key features, these structures serve as models for Toc75, albeit with low sequence identity (7%, 7%, and 8%, respectively).…”
Section: Discussionmentioning
confidence: 99%